Sarcopenic obesity is significantly associated with poorer overall survival after liver transplantation: a systematic review and meta-analysis - Huang, Hui-Bin; Zhu, Yi-Bing; Yu, Da-Xing (Frontiers in Nutrition, 2024)
Background: Sarcopenia has been shown to worsen survival after liver transplantation. However, it remains unclear whether coexisting sarcopenia and obesity, so-called sarcopenic obesity (SO), may also synergistically increase their adverse effects. This meta-analysis aimed to evaluate pre-transplant SO has an independent predictive value for survival in this population.We conducted this study according to the Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines. PubMed, Embase, Web of Science, Wanfang, CNKI, and Cochrane databases were searched through October 15, 2023, for studies with any study design evaluating the relationship between SO and posttransplant survival in patient undergoing liver transplantation . We used ROBINS-E to assess the study quality. The primary outcome was all-cause mortality at any length of follow-up. We calculated pooled odds risks (ORs) or hazard risks (HR) with 95% confidence intervals (CIs). Heterogeneity was quantified with I 2 -statistics. Subgroup analyses and publication bias evaluations were also conducted.We included nine cohort studies with 2416 patients. These studies were moderate to high quality. Pre-liver transplant patients commonly experience SO, with a mean prevalence as high as 34%. Overall, patients with SO had a significant increase in overall mortality compared with patients without SO by pooled studies reported both univariate analysis [HR=1.76, 95%C 1.33-2.33, P<0.0001] and multivariate analysis (HR=2.33, 95%CI 1.34-4.04, P=0.003). Similar results were also found when comparing patients with or without SO at one, three, and five years of OR=1.83, and OR=1.54, respectively). In addition, subgroup analysis based on studies that reported HRs of both sarcopenia and SO indicated both had independent negative effects on posttransplant survival.Conclusions: Our meta-analysis showed that SO occurs frequently in liver transplant patients. SO is associated with an increased risk of mortality in such patient populations.